Обгрунтування доцільності введення екологічного контролю енергетичних засобів при виробництві сільськогосподарської продукції - Мітков, Василь Борисович; Mitkov, Vasyl (Запоріжжя : 2022, 2022)
UA: В статті сформульовано принцип екологічного контролю енергетичних засобів при виробництві сільськогосподарської продукції. Представлено узагальнений коефіцієнт екологічної безпеки від впливу роботи МТА, розглядається тільки один фактор з узагальненого коефіцієнта, це вплив викидів відпрацьованих газів ДВЗ на екологічну безпечність проведення механізованих сільськогосподарських робіт. Для рішення вказаної проблеми постає питання, якими властивостями сільськогосподарський агрегат повинен відповідати, що б обумовлювати його придатність задовольняти певні вимоги екологічної безпеки. Іншими словами – як оцінити екологічну безпеку сільськогосподарського агрегату на етапі його проектування або модернізації, та як керувати екологічною безпекою в процесі функціонування сільськогосподарського агрегату. Виходячи з цього розробка методології оцінки рівня екологічної безпеки на етапі проектування, модернізації та функціонування сільськогосподарського агрегату є актуальним. EN: The article formulates the principle of environmental control of energy means in the production of agricultural products. A generalized coefficient of environmental safety from the impact of MTA is presented, only one factor from the generalized coefficient is considered, this is the impact of emissions of exhaust gases of internal combustion engines on the environmental safety of mechanized agricultural work. To solve this problem, the question arises, what properties an agricultural unit must meet in order to determine its suitability to meet certain environmental safety requirements. In other words – how to assess the environmental safety of an agricultural unit at the stage of its design or modernization, and how to manage environmental safety in the process of functioning of an agricultural unit. Based on this, the development of a methodology for assessing the level of environmental safety at the stage of design, modernization and operation of an agricultural unit is relevant. Now one of the main sources of imbalance of the natural environment is the work of machine-tractor units and mobile agricultural machinery. In general, the share of emissions is 60% of the total emissions of pollutants into the atmosphere and 70% of all mobile energy means. In this work, we consider only one factor is the impact of emissions of exhaust gases of internal combustion engines on the environmental safety of mechanized agricultural work. The optimal mode of operation of the engine of the tractor brand ХТЗ, from an environmental point of view, was adopted 1450-1850 rpm. At the same time, fuel consumption does not increase. It is possible to reduce emissions of the most significant in terms of volume and mass of the element of exhaust gases NOx if you limit the engine speed to 90% of the nominal. Emissions of CO and CH at this value of engine speed did not reach their maximum value.
Justification of the expediency of introducing environmental control of energy means in the production of agricultural products
Мітков В. Б. Обгрунтування доцільності введення екологічного контролю енергетичних засобів при виробництві сільськогосподарської продукції. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 3. C. 113-122.
Keywords: безпека; дизельний двигун; екологія; коефіцієнт; викиди; оберти двигуна; safety; diesel engine; ecology; coefficient; emissions; engine speed